Can algorithms reliably predict long-term unemployment in times of crisis? Evidence from the COVID-19 pandemic - Max Kunaschk; Julia Lang (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
In this paper, we compare two popular statistical learning techniques, logistic regression and random forest, with respect to their ability to classify jobseekers by their likelihood to become long-term unemployed. We study the performance of the two methods before the COVID-19 pandemic as well as the impact of the pandemic and its associated containment measures on their prediction performance. Our results show that random forest consistently out-performs logistic regression in terms of prediction performance, both, before and after the beginning of the pandemic. During the lockdowns of the first wave, the number of unemployment entries and the fraction of individuals that become long-term unemployed strongly increases, and the prediction performance of both methods declines. Finally, while the composition of the (long-term) unemployed changed at the beginning of the COVID-19 pandemic, we do not find systematic patterns across groups with different levels of labor market attachment or across different sectors of previous employment in terms of declines in prediction performance. – – In diesem Beitrag vergleichen wir zwei gängige Machine Learning Methoden, Logistische Regression und Random Forest, im Hinblick darauf, wie geeignet sie sind um Arbeitssuchende nach ihrer Wahrscheinlichkeit, langzeitarbeitslos zu werden, zu klassifizieren. Wir untersuchen die Prognosegüte der beiden Methoden vor der COVID-19-Pandemie sowie die Auswirkungen der Pandemie und der damit verbundenen Eindämmungsmaßnahmen auf ihre Vorhersagekraft. Unsere Ergebnisse zeigen, dass Random Forest Modelle Langzeitarbeitslosigkeit besser vorhersagen können als logistische Regressionsmodelle, sowohl vor als auch nach Beginn der Pandemie. Während des Lockdowns in der ersten Welle der Pandemie nimmt sowohl der Anteil der Personen, die sich arbeitslos melden, als auch der Anteil der Personen, die langzeitarbeitslos werden, stark zu. Gleichzeitig nimmt die Prognosegüte beider Methoden ab. Obwohl sich die Zusammensetzung der (Langzeit-)Arbeitslosen zu Beginn der COVID-19-Pandemie geändert hat, finden sich keine systematischen Unterschiede in der Prognosegüte zwischen arbeitsmarktnäheren und -ferneren Personen oder zwischen Personen, die in unterschiedlichen Branchen tätig waren.
Keywords: C53; J64; J68; J71; 330; COVID-19; long-term unemployment; machine learning; profiling